Trading on gender: the perversity of Asian labour exports as an economic development strategy. (1st April 2012) - Stuart Rosewarne
Abstract : The Philippines, Sri Lanka and Indonesia have promoted female labour migration as a strategy for generating export revenue in the form of income remittances in order to relieve external balance problems and as a source of investment funds. This strategy has relied largely on these countries' exploitation of their comparative advantage in the supply of workers for low-paid service sector work, and especially domestic work, on limited-term work permits and on conditions of employment that leave women vulnerable to a range of abuses. Labour market disadvantage has become institutionalised in this global labour market and, while there has been substantial growth in its scale, the evidence that labour exports provide the basis for delivering and maintaining economic benefits for individuals or the broader economy is questionable.